2009
DOI: 10.1111/j.1464-410x.2009.08796.x
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic skin response in patients with erectile dysfunction

Abstract: classified into three groups of normal or abnormal (increased) latency, and response blocking (no response), the last two being considered pathological conditions. RESULTSIn the penis, the mean ( SD ) SSR% was 52.8 (43.19)% and significantly lower than responses in hands and feet. There was a significant correlation of the SSR% between the palm of the hand and the sole of the foot ( P = 0.01) and between the sole of foot and penis ( P = 0.05). Diabetics showed a significant decrease ( P = 0.001) in the mean SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…This result is in line with the previous findings [9,14]. One study reported a significantly lower mean SSR% registered at the penis than that in the hands and feet [14]. Another study evaluated penile SSR (PSSR) in 20 ED patients aged 22 to 55 years (mean: 31 years; 11 cases occurred after pelvic fractures, 3 after severe injury of the perineum, 1 after fracture of the cervical spine, 1 due to hypertension, 2 with a history of severe masturbation, and 2 without known causes) and reported that PSSR in patients with ED had longer latencies and lower amplitudes compared with the control group [9].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This result is in line with the previous findings [9,14]. One study reported a significantly lower mean SSR% registered at the penis than that in the hands and feet [14]. Another study evaluated penile SSR (PSSR) in 20 ED patients aged 22 to 55 years (mean: 31 years; 11 cases occurred after pelvic fractures, 3 after severe injury of the perineum, 1 after fracture of the cervical spine, 1 due to hypertension, 2 with a history of severe masturbation, and 2 without known causes) and reported that PSSR in patients with ED had longer latencies and lower amplitudes compared with the control group [9].…”
Section: Discussionsupporting
confidence: 94%
“…2). This result is in line with the previous findings [9,14]. One study reported a significantly lower mean SSR% registered at the penis than that in the hands and feet [14].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations